Effect of prophylactic laser iridotomy on corneal endothelial cell density over 3 years in primary angle closure suspects. Issue 3 (30th November 2012) - Kumar, Rajesh S; Baskaran, Mani; Friedman, David S; Xu, Ying; Wong, Hon-Tym; Lavanya, Raghavan; Chew, Paul T; Foster, Paul J; Aung, Tin
Abstract : Objective: To assess the effect of prophylactic laser peripheral iridotomy (LPI) on corneal endothelial cell density (ECD) and morphology in primary angle closure suspects (PACS) over 3 years. Methods: In this prospective cohort study, subjects underwent LPI in one eye, while the fellow eye was untreated. Specular microscopy was performed at baseline and after 1 and 3 years. Central corneal ECD and morphology of both eyes were assessed using non-contact specular microscopy (Konan SP-9000LC, Konan Inc, Hyogo, Japan). Results: 230 subjects completed 3-year follow-up. The mean age was 62.5±8.0 years, and the majority of subjects were Chinese (92.3%) and women (75.4%). In eyes that underwent LPI, ECD was significantly lower at year 1 (2462.3, 95% CI 2414.5 to 2510.0, p<0.0001) and year 3 (2510.6, 95% CI 2462.1 to 2559.2, p=0.0006) compared with baseline (2609.1, 95% CI 2551.4 to 2666.7). There was also a significant decrease in ECD in fellow untreated eyes from baseline to year 1 (p<0.0001) and year 3 (p=0.01). The decrease in ECD at 3 years compared with the baseline in treated and untreated eyes was similar (2.1% vs 0.9%, p=0.20). Conclusions: In PACS eyes, there was decrease in ECD in LPI-treated and control eyes over 3 years, with no significant difference between groups.